Fostering Unity in Diversity: Ki Hadjar Dewantara’s Vision for Multicultural Education - Windria, Hening; Maksum, Arifin; Nurhasanah, Nina (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
Significant in building unity. To overcome this complex problem requires an education system that prioritizes unity with tolerance and respects cultural differences. This article explores Ki Hadjar Dewantara's vision in multicultural education as an effort to realize the motto